IDENTIFYING EA PRINCIPLES USING SWOT ANALYSIS (CASE STUDY OF E-COMMERCE PT. XYZ) - Rini Setyaningsih; Basuki Rahmad (Jurnal Sistem Informasi, 2015)
In current business practice, an integration between business and IT is important. Enterprise Architecture (EA) is one of the study that synergize IT and business. The principle will be use as the main base to designing appropriate EA. Before describing these principles, it is necessary to understand the real state of a company. It aims to make the situation as one as of benchmarks to describing state of the target. After designing state of the target, it will make processes of designing EA for a company is easier. This paper will use the SWOT analysis method to recognize their core competencies in order to determine the direction of an organization by analysing and positioning the organization’s resource and environment on four regions : Strengths, Weaknesses, Opportunities, and Threats. After an SWOT assessment, a mapping obtained wich that determines which quadrant position of the company. Every quadrant position will describe different strategies each other. From the obtained strategy, it will be describing target principles according to the position of a company based on the SWOT analysis. So the design EA for a company can start with a precise principles foundations.